Local Wisdom of the Community in Handling Mental Retardation People ( A Case Study of “Kampung Idiot” in Sidoharjo Village, Jambon District, Ponorogo Regency) - Hanif, Muhammad (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTSidoharjo village, in Jambon is one of villages in Ponorogo Regency, called as ‘Kampong Idiot’, since there are many villagers having mental retardation. They also have many disabilities, as a matter of fact they can survive and live quite longer. It certainly happens in accordance with the local wisdom of other villagers, the normal people who live in their surrounding. The research, therefore, aims to analyze and describe local wisdom of the community “Kampung Idiot” Sidoharjo Jambon Ponorogo in handling mental retardation people of Kampung Idiot in Sidoharjo village, Jambon district, Ponorogo regency. The research used descriptive-qualitative. The informants comprised of village officers, socialite, religion leader, youth and all family members of mental retardation people. Data were collected by using in-depth interview, observation, and documentation. Source triangulation was excuted in an effort to validate data and then the data were analyzed by using Strauss and Corbin’s Coding model.The local wisdom of Sidoharjo community in handling mental retardation people is a result of relationship among the people in the community, the people and their God, and the people and nature in their surrounding. The local wisdom can be seen from the community’s attitudeaccepting mental retardation people as the parts of the community and they are willing to help the mental retardation people do their personal, household and social activities. The local wisdom of the community seems to happen for (1) a belief in the existence of the mental retardation people is tribulation sent by God, providing deep meaning and boon that need to be faced, (2) they are social ethics and responsible moral for the social environment, (3) the norms include advices, prohibition, punishment, and wise words about life.Keywords: local wisdom, attitude, mental retardation peopleABSTRAKDesa Sidoharjo Jambon merupakan salah satu kampung di Kabupaten Ponorogo yang disebut “kampung idiot” karena banyak warganya yang mengalami retardasi mental. Warga retardasi mental di kampung ini memiliki banyak keterbatasan namun dapat melangsungkan hidupnya dalam kurun waktu yang relatif lama. Hal itu tentunya terkait dengan sikap arif warga masyarakat di lingkungan sekitarnya. Adapun tujuan penelitian ini adalah untuk menganalisis dan mendeskripsikan kearifan lokal masyarakat Sidoharjo dalam menyikapi warga retardasi mental di “kampung idiot” Sidoharjo Jambon. Penelitian ini mengunakan pendekatan kualitatif-deskriptif. Informan terdiri dari pejabat pemerintah desa, tokoh; masyarakat, agama, dan pemuda, serta keluarga warga retardasi mental. Pengambilan datanya menggunakan wawancara mendalam, observasi, dan pencatan dokumen. Validasi data dengan triangulasi sumber dan analisis datanya dengan model coding Strauss dan Corbin. Hasil penelitian menunjukkan bahwa kearifan lokal masyakat dalam menyikapi warga retardasi mental merupakan hasil dari relasionalitas diantara warga masyarakat, masyarakat dengan Tuhan dan alam. Masyarakat menerima warga retardasi mental sebagai bagian dari dirinya dan berusaha membantunya agar mampu menjalankan aktivitas pribadi, keluarga, dan sosial. Kearifan lokal masyarakat tersebut dipredisposisi oleh; (1) keyakinan bahwa warga retardasi mental merupakan ujian Tuhan yang harus disikapi karena mengandung arti serta hikmah, (2) etika sosial dan tanggungjawab secara moral terhadap lingkungan sosial, (3) norma-norma yang berupa anjuran-anjuran, larangan-larangan, sanksi, dan ungkapan kebijaksanaan akan kehidupan.Kata kunci: kearifan lokal, sikap, warga retardasi mental